The Mexican Peso Crisis : Overview and Analysis of Credibility Factors - Masson, Paul (IMF Working Papers; Working Paper ;, 1996)
This paper examines credibility and reputational factors in explaining the December 1994 crisis of the Mexican peso. After reviewing events leading to the crisis, a model emphasizing the inflation-competitiveness trade-off is presented to explain the formation of devaluation expectations. Estimation results indicate that investors appear to have seriously underestimated the risk of devaluation, despite early warning signals. The collapse of confidence that followed the December 20 devaluation may have been the result of a shift in the perceived commitment of the authorities to exchange rate stability.